Editorial: Environmental Issues and Globalization: A Three State-Market Approaches - Mahayasa, Dias Pabyantara Swandita (JUSS (Jurnal Sosial Soedirman), 2024)
Environmental Issues and Globalization: A Three State-Market Approaches